INTERNALISASI PENDIDIKAN IMAN KEPADA ANAK DALAM PERSPEKTIF ISLAM - Silahuddin Silahuddin (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2016)
Children are human beings who are in need to be nurtured, guided and developed. All of their potency should be developed positively in education. Educating childrenâ€™s faith by using LuqmÄn al-á¸¤akÄ«m ways will lead them to be the most precious blessing creatures in this world and the hereafter. Keywords: